KCNA2 IgG autoimmunity in neuropsychiatric diseases - Arlt, Friederike Antonia; Miske, Ramona; Machule, Marie-Luise; Broegger Christensen, Peter; Mindorf, Swantje; Teegen, Bianca; Borowski, Kathrin; Buthut, Maria; Rößling, Rosa; Sánchez-Sendín, Elisa; Hoof, Scott van; Cordero Gómez, César; et al. (Brain, behavior and immunity, 2024)
Background - Autoantibodies against the potassium voltage-gated channel subfamily A member 2 (KCNA2) have been described in a few cases of neuropsychiatric disorders, but their diagnostic and pathophysiological role is currently unknown, imposing challenges to medical practice. - Design / Methods. - We retrospectively collected comprehensive clinical and paraclinical data of 35 patients with KCNA2 IgG autoantibodies detected in cell-based and tissue-based assays. Patients’ sera and cerebrospinal fluid (CSF) were used for characterization of the antigen, clinical-serological correlations, and determination of IgG subclasses. - Results - KCNA2 autoantibody-positive patients (n = 35, median age at disease onset of 65 years, range of 16-83 years, 74 % male) mostly presented with cognitive impairment and/or epileptic seizures but also ataxia, gait disorder and personality changes. Serum autoantibodies belonged to IgG3 and IgG1 subclasses and titers ranged from 1:32 to 1:10,000. KCNA2 IgG was found in the CSF of 8/21 (38 %) patients and in the serum of 4/96 (4.2 %) healthy blood donors. KCNA2 autoantibodies bound to characteristic anatomical areas in the cerebellum and hippocampus of mammalian brain and juxtaparanodal regions of peripheral nerves but reacted exclusively with intracellular epitopes. A subset of four KCNA2 autoantibody-positive patients responded markedly to immunotherapy alongside with conversion to seronegativity, in particular those presenting an autoimmune encephalitis phenotype and receiving early immunotherapy. An available brain biopsy showed strong immune cell invasion. KCNA2 autoantibodies occurred in less than 10 % in association with an underlying tumor. - Conclusion - Our data suggest that KCNA2 autoimmunity is clinically heterogeneous. Future studies should determine whether KCNA2 autoantibodies are directly pathogenic or develop secondarily. Early immunotherapy should be considered, in particular if autoantibodies occur in CSF or if clinical or diagnostic findings suggest ongoing inflammation. Suspicious clinical phenotypes include autoimmune encephalitis, atypical dementia, new-onset epilepsy and unexplained epileptic seizures.
Online verfügbar 2 February 2024, Version des Artikels 8 February 2024
Gesehen am 05.07.2024